The Influence of Food Quality, Service Quality, and Service Recovery on Consumer Satisfaction at Geprek Assalam 99 Plaosan Magetan - Afif Sultoni; Sri Hartono; Wijianto (PT. Anagata Sembagi Education, 2024)
The business world has quite a variety of problems, especially in terms of the quality of what is marketed by business actors, for that researchers conduct in-depth research in terms of consumer satisfaction. This study took the object of Assalam 99 Plaosan Magetan geprek consumers. The method used in this study is a quantitative method using multiple linear regression analysis, with hypothesis testing and assisted by determination analysis and instrument testing in the form of validity and reliability. This research uses primary data with a tool in the form of a questionnaire which is distributed directly to related objects in this scientific research. Research shows that food quality has a significant effect on consumer satisfaction. Service quality has a significant effect on customer satisfaction. Service recovery has a significant effect on customer satisfaction.